TANTANGAN GURU DALAM MENERAPKAN PEMBELAJARAN JARAK JAUH (PJJ) DI ERA TEKNOLOGI DAN KOMUNIKASI - Yuliansyah, Arief; Agus Setiawan; Rama Wijaya Abdul Rojak; Udin Syaefuddin Sa’ud; Atep Sujana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the challenges faced by teachers in implementing distance learning (PJJ) in the era of technology and communication. This research uses the Systematic Literature Review (SLR) method, referring to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), to examine documents from Google Scholar within the range of 2010 to 2024. The search for journal articles was conducted using Publish or Perish with the keywords